Isometric Exercise Training for Managing Vascular Risk Factors in Mild Cognitive Impairment and Alzheimer’s Disease - Hess, Nicole C. L.; Smart, Neil A. (Frontiers in Aging Neuroscience, 2017)
Abstract Alzheimer’s disease (AD) is the most common form of dementia diagnosed amongst the elderly. Mild cognitive impairment (MCI) is a condition often indicative of the earliest symptomatology of AD with 10-15% of MCI patients progressing to a diagnosis of AD. Individuals with a history of vascular risk factors (VRF’s) are considered high risk candidates for developing cognitive impairment in later life. Evidence suggests that vascular injury resulting from untreated VRF’s promotes progression from MCI to AD and exacerbates the severity of dementia in AD, and neuroimaging studies have found that the neurodegenerative processes associated with AD are heavily driven by VRF’s that promote cerebral hypoperfusion. Subsequently, common links between vascular disorders such as hypertension and neurodegenerative disorders such as AD include compromised vasculature, cerebral hypoperfusion and chronic low grade inflammation (a hallmark of both hypertension and AD). Exercise has been demonstrated to be an effective intervention for blood pressure management, chronic low grade inflammation, and improvements in cognition. Data from recent analyses suggests that isometric exercise training (IET) may improve vascular integrity and elicit blood pressure reductions greater than those seen with dynamic aerobic and resistance exercise. IET may also play an effective role in the management of VRF’s at the MCI stage of AD and may prove to be a significant strategy in the prevention, attenuation or delay of progression to AD. A plausible hypothesis is that the reactive hyperaemia stimulated by IET initiates a cascade of vascular, neurotrophic and neuro-endocrine events that lead to improvements in cognitive function.